Efficient ecofriendly synthesis of pyrazole acryloyl analogs by amino acid catalysis - Chaudhry, F.; Asif, N.; Shafqat, S.S.; Khan, A.A.; Munawar, M.A.; Khan, M.A. (Taylor and Francis Inc., 2016)
An easy and effective green approach of Knoevenagel condensation and arylidene formation with the substrates involves pyrazole-3-carbaldehydes and active methylenes under catalytic action of glycine (the simplest amino acid) in dimethylsulfoxide. These reactions were successfully carried out at room temperature.